HARMONI BUDAYA DALAM RITUAL METHIKAN DI MASYARAKAT DESA PANGKAH TEGAL - Elya Munfarida (IAIN Purwokerto, 2011)
Methikan Ceremony, also called siametan gilingan, is one of the ceremonies held by the community of Pangkah and Sugar Factory of Pangkah as the organizer. The ceremony was held to mark the harvest and the beginning of milling sugar canes at the same time. The ceremony was preceded by harvesting (Java: methik) sugar canes on sugar plantations owned by farmers and factories to be treated as a pair of bride and bridegroom. The implementation of methikan ceremony was based on the religious system that can not be separated from the view of life (weltanchaung) and the Javanese world view on the achievement of certain spiritual values such as calmness, serenity and inner balance through the appreciation of society, nature and supernatural as an inseparable unity that must be actualized in appropriate actions.